2019
DOI: 10.21608/asejaiqjsae.2019.40780
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Behavior of Some Rice Genotypes under Normal and High Temperature Stress

Abstract: Thirteen rice genotypes were grown in the two successive rice seasons 2017 and 2018 to assess the presence of variability for desired traits and estimate genetic parameters and correlations for traits under normal and heat stress conditions. Analysis of variance revealed significant differences due to environments, genotypes and their interaction for all studied characteristics in both seasons. The estimates of genotypic (GCV) and phenotypic (PCV) coefficient of variation were highly significant for all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…CO51 invariably recorded a higher panicle weight of 3.21 g under control, but 24.16 percent reduction of panicle weight was recorded in comparision to N22 (10.10%) at HTS (Table . 1). These results were similar to the findings of Gaballah and Abu (2019) where panicle length and panicle weight of rice genotypes were reduced due to heat stress.…”
Section: Yield Responsessupporting
confidence: 90%
See 1 more Smart Citation
“…CO51 invariably recorded a higher panicle weight of 3.21 g under control, but 24.16 percent reduction of panicle weight was recorded in comparision to N22 (10.10%) at HTS (Table . 1). These results were similar to the findings of Gaballah and Abu (2019) where panicle length and panicle weight of rice genotypes were reduced due to heat stress.…”
Section: Yield Responsessupporting
confidence: 90%
“…During ripening, the panicle is a highly sensitive organ to high-temperature stress (Morita et al, 2004). Panicle length and panicle weight in rice may get affected as temperature attains beyond (Gaballah and Abu, 2019). Paddy yield had a strong genetic correlation with the number of grains per panicle and 1000 grain weight (Karwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between grain yield and flag leaf angle was positive and significant under normal condition while it was negative and highly significant under heat stress condition indicating that genotypes with erect flag leaf are more desirable for cultivating in high temperature regions. A similar result was obtained by Gaballah and Abu El-Ezz (2019) who reported that flag leaf angle was highly significant positive correlated with leaf rolling and sterility %, and highly significant negative correlated with panicles plant -1 , panicle weight and grain yield plant -1 under normal and heat stress conditions. The correlation between grain yield and flag leaf area and plant height traits was negative under normal condition but it was positive under stress condition meaning that those traits are good indicators for tolerance under stress condition.…”
Section: Phenotypic Correlation Coefficientsupporting
confidence: 87%
“…Genetic distance was correlated positively with grain length, panicle number and length: width ratio and correlated negatively with grain width, grain yield and seed setting rate [26,27]. Highly positive and significant phenotypic correlations were observed between yield index and leaf rolling, sterility percentage [28].…”
Section: Discussionmentioning
confidence: 99%